Interiority From the Body, Mind, and Culture - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2022)
Within the interior occupation, the human body and interior are always interacting. Body-interior relation is a key idea in understanding the human body's presence, experience, and performance in interior space. The body and the interior can define, command, and affect each other. The transactional perspective in environmental psychology emphasises the reciprocity between body and environment. Awareness of these reciprocal relationships becomes a key in understanding the interior as a stage for the human body and its dynamic processes. This issue of Interiority presents a collection of studies that situate the human body as an inherent part of the interior environment from various perspectives: neuroscience, psychology, culture, religion, gender, and tradition. These articles present various ways in which the interior becomes a manifestation of the dynamic human body-space relations. They demonstrate attempts to examine interiority through various cases and contexts defined by individual experiences, dynamic social roles and relationships, and cultural traditions.